La presse de Syrie et du Liban entre les deux guerres (1918-1939) - Nadine Méouchy (Revue des Mondes Musulmans et de la Méditerranée)
The unprecedented development of the press in Syria and Lebanon during the Inter War years, is in keeping with this period of intense political mobilization, of transformations in public life and of an increase in education. It is during these years, in which the press appears as a privileged access to public speech, that a new, young and committed profession, that of the journalists, becomes established. The press which acts as a medium and a mirror of these different changes also shows how the different characters of the two capitals, recently promoted as such, Beirut and Damascus, are asserted.